Application of Internet of Things (IoT) Technology to KWT “Sido Makmur” Oyster Mushroom Cultivation - Widyasmoro Widyasmoro; Taufiq Hidayat; Tony K Hariadi; Norazhar Bin Mohamed Sepet; Wee Eng Soon (Universitas Muhammadiyah Yogyakarta, 2023)
Ngaran Hamlet, an area in Gilangharjo Village, Pandak District, Bantul Regency, DIY, has a Women Farmers Group (KWT),